PO 8719 Introducing a new africa meningitis network – a north-south collaboration. (24th April 2019) - Mosepele, Mosepele; Kanyama, Cecilia; Meya, David; Cresswell, Fiona; Chammard, Timothee; Mwandumba, Henry; Meintjes, Graeme; Mfinanga, Godfrey S; Ndhlovu, Chiratidzo; Jarvis, Joseph
Abstract : Background: Central nervous system infections, including meningitis, continue to cause significant morbidity in Africa. HIV has contributed to the epidemiology of CNS infections in this setting. Notable advances in the study of CNS infections by several groups have demonstrated the utility of new diagnostic strategies and impact of novel treatment strategies. However, efforts to coordinate meningitis research in Africa, and between Africa and the rest of the world remain very limited. Methods: In a bid to promote a coordinated study of CNS infections across Africa, and in collaboration with other meningitis groups globally, the researchers of the AMBITION study (High Dose Ambisome on a Fluconazole Backbone for Cryptococcal Meningitis Induction Therapy in Sub-saharan Africa: A Randomised Controlled Non-inferiority Trial) are leveraging the EDCTP support for the AMBITION trial to set up an Africa Meningitis Trials Network. Results: The Africa Meningitis Trials Network (AMNET) was launched in Malawi in early 2018. Main achievements since the launch of the network, include an internal review of meningitis research across network sites and launch of the network website. The network also has two study protocols pending ethics review at all sites. These studies will provide much needed information on resources available for meningitis care, research and provide a baseline epidemiology of meningitis in Africa. Conclusion: AMNET provides a rare opportunity for investigators interested in meningitis research to leverage the ongoing AMBITION trial to conduct Africa-wide preliminary research on meningitis. The network is recruiting additional members in Africa and globally to collaborate on meningitis research, and also apply for research funding to support meningitis work. Anyone interested in knowing more about the network should contact the AMNET communications officer, Ms Phum'lani Machao, phumlani.machao@gmail.com